A randomized trial Examining The Impact Of Communicating Genetic And Lifestyle Risks For Obesity. Issue 12 (December 2016) - Wang, Catharine; Gordon, Erynn S.; Norkunas, Tricia; Wawak, Lisa; Liu, Ching‐Ti; Winter, Michael; Kasper, Rachel S.; Christman, Michael F.; Green, Robert C.; Bowen, Deborah J.
Abstract : Objective: Genetic testing for obesity is available directly to consumers, yet little is understood about its behavioral impact and its added value to nongenetic risk communication efforts based on lifestyle factors. Methods: A randomized trial examined the short‐term impact of providing personalized obesity risk information, using a 2 × 2 factorial design. Participants were recruited from the Coriell Personalized Medicine Collaborative (CPMC) and randomized to receive (1) no risk information (control), (2) genetic risk, (3) lifestyle risk, or (4) combined genetic/lifestyle risks. Baseline and 3‐month follow‐up survey data were collected. Analyses examined the impact of risk feedback on intentions to lose weight and self‐reported weight. Results: A total of 696 participants completed the study. A significant interaction effect was observed for genetic and lifestyle information on intent to lose weight ( P = 0.0150). Those who received genetic risk alone had greater intentions at follow‐up, compared with controls ( P = 0.0034). The impact of receiving elevated risk information on intentions varied by source and combination of risks presented. Non‐elevated genetic risk did not lower intentions. No group differences were observed for self‐reported weight. Conclusions: Genetic risk information for obesity may add value to lifestyle risk information depending on the context in which it is presented.